Факторы, влияющие на появление транзитных метастазов меланомы кожи нижних конечностей - Ефетов, С.К.; Телькиева, Г.Н.; Ефетова, Т.С. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2010)
Ретроспективный анализ историй болезни 336 больных меланомой кожи нижних конечностей показал статистически достоверную зависимость возникновения транзитных метастазов (ТМ) от глубины инвазии по Clark, от частоты поражения регионарных лимфатических узлов (ЛУ), от тактики лечения (лимфодиссекция при отсутствии поражения ЛУ достоверно повышает частоту ТМ) и от локализации опухоли. Ключевые слова: меланома
кожи, транзитные метастазы. Retrospective analysis of medical history of 336 patients with skin melanoma of lower extremity reveal statistical reliable dependence of appearance of transit metastasis from invasion depth according to Clark, from frequency of lesion of regional lymphatic nodes from treatment tactics (lymphodissection in the absence of lesion of regional lymphatic nodes reliable increase the frequency of transit metastasis from tumor localization. Key Words: skin melanoma, transit metastasis.